2018
DOI: 10.31234/osf.io/g9pxn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced association-memory for negative information: impact of confidence and interactive imagery during study

Abstract: Although item-memory for emotional information is enhanced, memory for associations between items is impaired for negative, emotionally arousing compared to neutral information. We tested two possible mechanisms underlying this impairment, using picture pairs: 1) higher confidence in one’s own ability to memorise negative information may cause participants to under-study negative pairs; 2) better interactive imagery for neutral pairs could facilitate association-memory for neutral more than for negative pairs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…The fact that emotion enhanced association-memory stands in contrast to prior studies, using paired-associates tasks, which have found that when a negative item is present it leads to impairments in cued recall (e.g., Caplan et al, 2019;Madan et al, 2012Madan et al, , 2017Mao et al, 2017;Rimmele et al, 2011;Touryan et al, 2007). The current study instead found that negative items lead to enhanced memory for the associated target.…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that emotion enhanced association-memory stands in contrast to prior studies, using paired-associates tasks, which have found that when a negative item is present it leads to impairments in cued recall (e.g., Caplan et al, 2019;Madan et al, 2012Madan et al, , 2017Mao et al, 2017;Rimmele et al, 2011;Touryan et al, 2007). The current study instead found that negative items lead to enhanced memory for the associated target.…”
Section: Discussioncontrasting
confidence: 99%
“…Although it is well-established that emotional stimuli are better remembered than neutral stimuli, there is also evidence that negative emotion can impair intentional association learning when the to-be-associated stimuli are unrelated (Touryan et al, 2007;Zimmerman & Kelley, 2010;Madan et al, , 2017aBisby & Burgess, 2014;Bisby et al, 2018;Caplan et al, 2019;Palombo et al, 2021). Notably, this occurs even when items are presented relatively slowly and sequentially and when there is sufficient evidence of item-memory but impaired association-memory (Madan et al 2017).…”
Section: Introductionmentioning
confidence: 99%